2021
DOI: 10.1002/adma.202100854
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Trap‐Assisted Triplet Generation in Lead Halide Perovskite Sensitized Solid‐State Upconversion

Abstract: Photon upconversion via triplet–triplet annihilation (TTA) has promise for overcoming the Shockley–Queisser limit for single‐junction solar cells by allowing the utilization of sub‐bandgap photons. Recently, bulk perovskites have been employed as sensitizers in solid‐state upconversion devices to circumvent poor exciton diffusion in previous nanocrystal (NC)‐sensitized devices. However, an in‐depth understanding of the underlying photophysics of perovskite‐sensitized triplet generation is still lacking due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 38 publications
5
60
1
Order By: Relevance
“…The charge carrier dynamics of perovskites are correlated to grain size, , crystallinity, as well as available trap density, , which are tunable by the perovskite thickness as well as the fabrication methods, e.g., the utilized antisolvent or antisolvent dripping time, , and the illumination time. , It has been observed that the underlying charge carrier dynamics directly influence the UC efficiency, indicating that both bulk and surface trap densities are critical factors in the UC process, despite it being thought of as an interfacial process . Longer perovskite PL lifetimes result in a higher UC QY .…”
Section: Lead Halide Perovskite Triplet Sensitizersmentioning
confidence: 99%
See 2 more Smart Citations
“…The charge carrier dynamics of perovskites are correlated to grain size, , crystallinity, as well as available trap density, , which are tunable by the perovskite thickness as well as the fabrication methods, e.g., the utilized antisolvent or antisolvent dripping time, , and the illumination time. , It has been observed that the underlying charge carrier dynamics directly influence the UC efficiency, indicating that both bulk and surface trap densities are critical factors in the UC process, despite it being thought of as an interfacial process . Longer perovskite PL lifetimes result in a higher UC QY .…”
Section: Lead Halide Perovskite Triplet Sensitizersmentioning
confidence: 99%
“…Three different approaches have been utilized to create the organic layer capable of UC. The organic thin film can be solution cast onto the perovskite film, , the organic molecules can be directly included into the antisolvent, or thermal evaporation can be used. , The local and long-range order of the rubrene molecular arrangement, as well as the rubrene thickness, are factors that play an important role in the UC process, further tunable by the utilized solvent or post-fabrication annealing steps to increase crystallinity.…”
Section: Upconversion Process In Rubrenementioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, the exact mechanism of triplet sensitization is still unclear. [30][31][32][33] Understanding the fundamental mechanism of triplet sensitization at the perovskite/organic interface will be the key in further improving perovskite-based UC, as it will unlock engineering pathways to further increase the device performance.…”
mentioning
confidence: 99%
“…Particularly, it emphasizes that only a small fraction of free charges created upon photoexcitation are successfully extracted and return upconverted photons despite the long-lived nature of the free carriers in the perovskite, which should allow a large number of charges to be extracted within their lifetime. 23,28 Possible causes include localized states mediating electron and hole transfer and limiting the number of generated triplet states 30,31 and short-lived transient states (e.g. hot carriers) being involved in the triplet generation process.…”
mentioning
confidence: 99%